Corrosion Properties of Various Copper Pipes Joints - Tatiana Liptakova; Monika Halamova; Ayman Alaskari; Martin Lovisek; Maxim Puchnin (Communications - Scientific letters of the University of Zilina, 2014)
The paper presents the experimental results of various Cu pipes joint corrosion behavior. Joining of copper pipes used for liquid media transport can be made as demountable and fixed joints. The object is to study corrosion resistance of the joints created by soft soldering, hard soldering and fitting. Corrosion properties were investigated by long-term experiment in two identical experimental devices in stagnant and flowing conditions. The experimental environment was water solution of the 3% NaCl, temperature was kept 20° C for 16 hours and 8 hours 80° C per day. In one of the devices for 8 hours the experimental solution was flowing by the input speed 0.27m.s -1. In the second one no flow was applied. Evaluation of the joints corrosion attacks was performed visually, by light and scanning electron microscopy.